Curadoria e sustentabilidade no factors: estudos de caso de obras em arte, ciência e tecnologia - Oliveira, Fabíola Assunção de (2023)
This dissertation presents a research situated in the field of History, Theory and Criticismo of Art. Its general objective is to investigate and discuss a curatorial proposal from the case study of three contemporary works of Art, Science and Technology by the focus of Sustainability, exhibited at the Festival Art Science Tecnology/FACTORS. There is a need, from Belting (2012) and Cauquelin (2005), to reconfigure the History of Art and update the curatorship to follow the artist's production with his time. Machado (2007) and Sogabe (2019) bring the importance of artistic manifestation in art and technology as instigators and questioners of everyday life. With Couchot (2018), the association of sciences is added, allowing greater collaboration between the areas, which enriches the debate on sustainability, in addition to the importance of transdisciplinarity by Morin (2005) and Santos, N. (2021). For the development of this work, a qualitative approach is adopted, with research and data collection in different areas of knowledge to be discussed in the light of the Visual Arts. The works Nós Abelhas (2016) by Malu Fragoso, Tradescantia (2018) by Claudia Valente and Estudo Imaginário Sobre Seres Possíveis (2019) by Laura Zingariello, presented in FACTORS issues 5.0 and 7.0, represent the relationship of sustainability with the environment, highlighting connections through the Festival’s transdisciplinary curatorial argument each year. Thus, relating them to the sustainable theme becomes the guiding thread for the project, that brings together in the spatialities of air, soil and sea curatorial strategies thought beyond the environmental, transdisciplinarity to expand its concept due to the freedom given to contemporary art to discuss current issues.